2015
DOI: 10.1080/00958972.2015.1048239
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and characterizations of tetracyanoplatinate(II) complexes with 2-pyridineethanol

Abstract: New cyanide-bridged heteronuclear polymeric complexes, [Cu(hepH) 2 Pt(μ-CN) 2 (CN) 2 ] n (1), [Zn (hepH) 2 Pt(μ-CN) 2 (CN) 2 ] n (2), and [Cd(hepH) 2 Pt(μ-CN) 2 (CN) 2 ] n (3) (2-pyridineethanol abbreviated to hepH), have been synthesized and characterized by elemental analysis, FT-IR and Raman spectroscopies, thermal analysis, and single-crystal X-ray diffraction techniques. Hydrogen bonds play very important roles in the construction of supramolecular structures. From the crystallographic data, it was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Other solution‐based syntheses of ZnPt(CN) 4 have been reported, but the products not characterized. The addition of excess Na 2 Pt(CN) 4 to an aqueous solution of Zn(NO 3 ) 2 generated a white precipitate exhibiting a green luminescence; no further characterization of this product was described .…”
Section: Resultsmentioning
confidence: 99%
“…Other solution‐based syntheses of ZnPt(CN) 4 have been reported, but the products not characterized. The addition of excess Na 2 Pt(CN) 4 to an aqueous solution of Zn(NO 3 ) 2 generated a white precipitate exhibiting a green luminescence; no further characterization of this product was described .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we have reported the tetracyanonickelate(II), tetracyanopalladate(II) and tetracyanoplatinate(II) complexes with hepH [12][13][14]. As a part of our continuing research on cyanide complexes, herein we described the syntheses and characterizations of tetracyanonickelate(II) complexes with different metals such as Fe(II), Co(II) and Ni(II).…”
Section: Introductionmentioning
confidence: 98%
“…13,14 Planar cyano metal anions are widely used to design these complexes. 14,15,16,17 Especially, square-planar tetra cyanometallate(II) ions, i.e. [M(CN) 4 ] 2-(M(II) = Ni, Pd or Pt), have been widely used as building blocks of Hofmann type structures.…”
Section: Introductionmentioning
confidence: 99%